A two-step strategy for the preparation of 6-deoxy-l-sorbose. Issue 17 (1st September 2016) - Wen, Liuqing; Huang, Kenneth; Zheng, Yuan; Liu, Yunpeng; Zhu, He; Wang, Peng George
Graphical abstract: Abstract: A two-step enzymatic strategy for the efficient and convenient synthesis of 6-deoxy-l -sorbose was reported herein. In the first reaction step, the isomerization ofl -fucose (6-deoxy-l -galactose) tol -fuculose (6-deoxy-l -tagatose) catalyzed byl -fucose isomerase (FucI), and the epimerization ofl -fuculose to 6-deoxy-l -sorbose catalyzed byd -tagatose 3-epimerase (DTE) were coupled with the targeted phosphorylation of 6-deoxy-l -sorbose by fructose kinase from human (HK) in a one-pot reaction. The resultant 6-deoxy-l -sorbose 1-phosphate was purified by silver nitrate precipitation method. In the second reaction step, the phosphate group of the 6-deoxy-l -sorbose 1-phosphate was hydrolyzed with acid phosphatase (AphA) to produce 6-deoxy-l -sorbose in 81% yield with regard tol -fucose.